The determinants of loan contracts to business firms - Thi Thu Trà Pham; Robert Lensink (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
This paper deals with loan contracting from a private bank in Vietnam. We focus on the main loan contract features that the bank uses in lending to business firms, namely loan maturity, collateral and loan interest rate. Based upon the simultaneous equation model of Dennis et al. (2000) and the bank's loan contracting policies, we examine the possible interdependency of the three different loan contract terms. Also, we try to determine which firm characteristics and exogenous factors are relevant for loan contracts. We find strong interdependencies between these contract terms with significant bi-directional relationships between collateral and loan maturity, loan rate and loan maturity, and a uni-directional relationship between loan rate and collateral. The conflicting signs within the collateral–loan maturity relationship and the loan interest rate–loan maturity relationship can be explained by our hypothesis that the choice for a certain loan maturity is primarily determined by borrowers' behaviors, whereas the loan rate and the collateral requirements are primarily determined by banks policies. In addition, our results support the relevance of firm quality, agency costs of debt and relationship lending in loan contract design.
Keywords: G14; G21; C31; 330; contract design; collateral; interest rate; maturity; Kreditgeschäft; Privatbank; Vietnam